VALUE ORIENTATION AND SPIRITUAL INTELLIGENCE OF ADOLESCENTS: A CORRELATIONAL STUDY - Bhasin, Geeta; Raj, Anoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study contemplated to ascertain significance of value orientation and impact of spiritual intelligence on value orientation in the life of adolescents based on gender and type of school boards. Study conducted on 900 adolescents’ boys and girls of senior secondary school of three districts (Meerut, Moradabad, and Bareilly) of UP state. A stratified random sampling technique used to select the sample form school population. Spiritual Intelligence scale by Dr. K.S. Misra and value orientation scale by Dr. Gururaja C.S were used for data collection form the the sample. To evaluate and make conclusions between the groups and boards of teenage boys and girls, the data was analysed using the t-test and correlation, as these statistical methods seem appropriate. The research indicated that spiritual intelligence (SI) had an important effect on the value orientation of adolescent girls but not boys. Girls with greater spiritual intelligence levels had higher value orientation scores, whereas boys did not differ significantly across spiritual intelligence levels. This suggests that spiritual intelligence affects value orientation differently depending on gender. Furthermore, variations in the relation between spiritual intelligence and value orientation were noticed among school boards (UP, CBSE, and ICSE), proving that the educational context also influences this dynamic. Overall, these findings emphasise the need of taking gender and educational environment into consideration when evaluating the impact of spiritual intelligence on the behaviour of adolescent’s value orientations.